PARTEA DE MĂREȚIE CUJBIANĂ DINSPRE NECESITATE ȘI ÎNTREG - PALLADI, Tudor (BIBLIOPOLIS, 2020)
The study of the poet and literary critic Theodor Pallady presents a comprehensive analysis of monographic The name on the temple of truth: Sergiu Victor Cujbă writer (1875-1937) by dr. Claudia Slutu Grama, poet, librarian. Sergiu Victor Cujbă is the author of lyric poems Homeland and Freedom (1916) and Bessarabian Songs (1919). Lately, the writer, was forgotten by some historians and literary anthologist. Therefore, Mrs C. Slutu Grama started the investigation and reassessment of this personality. The researcher points out, rightly, that “although Cujbă was forced to abandon for a while Bessarabia, the love that has kept for her native land, oppressed peasants never left his heart.” It is worth mentioning that the scientific investigation on the life and work of Sergiu V. Cujbă was based on traditional literary historical survey, focusing on the rigorous text analysis and a complex approach to his life and work, that represents the “novelty of the research”. It follows therefrom its usefulness for all readers and the „contribution” to a better understanding of the Bessarabian interwar literary phenomenon.